Audit Quality for US‐listed Chinese Companies. Issue 2 (27th December 2016) - Dang, Chien Minh; Fargher, Neil; Lee, Gladys
Abstract : PCAOB Staff Audit Practice Alert No. 6 raised concerns regarding the quality of audit reports on financial statements filed by issuers with substantially all of their operations outside of the US. An area of specific concern is the audit of companies with operations predominantly based in mainland China. Using a sample of Chinese companies listed in the US, we examine whether measures of audit quality are affected by the location of the auditor. We find some evidence of higher levels of discretionary accruals when a US‐listed Chinese firm is audited by a small US auditor.